Synthesis and Reactivity of a Cobalt-Supported Singlet Nitrene - Mao, Weiqing; Zhang, Zihan; Fehn, Dominik; Jannuzzi, Sergio A.V.; Heinemann, Frank Wilhelm; Scheurer, Andreas; van Gastel, Maurice; DeBeer, Serena; Munz, Dominik; Meyer, Karsten (Journal of the American Chemical Society, 2023)
The synthesis, characterization, and reactivity of a series of cobalt terminal imido complexes supported by an N-anchored tripodal tris(carbene) chelate is described, including a Co-supported singlet nitrene. Reaction of the CoI precursor [(TIMMNmes)CoI](PF6) (TIMMNmes = tris-[2-(3-mesityl-imidazolin-2-ylidene)-methyl]amine) with p-methoxyphenyl azide yields a CoIII imide [(TIMMNmes)CoIII(NAnisole)](PF6) (1). Treatment of 1 with 1 equiv of [FeCp2](PF6) at −35 °C affords a formal CoIV imido complex [(TIMMNmes)Co(NAnisole)](PF6)2 (2), which features a bent Co-N(imido)-C(Anisole) linkage. Subsequent one-electron oxidation of 2 with 1 equiv of AgPF6 provides access to the tricationic cobalt imido complex [(TIMMNmes)Co(NAnisole)](PF6)3 (3). All complexes were fully characterized, including single-crystal X-ray diffraction (SC-XRD) analyses, infrared (IR) vibrational, ultraviolet/visible (UV/vis) electronic absorption, multinuclear NMR, X-band electron paramagnetic resonance (EPR), electron nuclear double resonance (ENDOR), and high-energy-resolution fluorescence-detected X-ray absorption spectroscopy (HERFD XAS). Quantum chemical calculations provide additional insight into the electronic structures of all compounds. The dicationic CoIV imido complex 2 exhibits a doublet ground state with considerable imidyl character as a result of covalent Co-NAnisole bonding. At room temperature, 2 readily converts to a CoII amine complex involving intramolecular C-H bond amination. Electronically, tricationic complex 3 can be understood as a singlet nitrene bound to CoIII with significant CoIV imidyl radical character. Verifying the pronounced electrophilicity, nucleophiles such as H2O and tBuNH2 add to 3─analogous to the parent free nitrene─in the para position of the aromatic substituent, thus, clearly corroborating singlet nitrene-type reactivity.
CRIS-Team Scopus Importer:2023-07-21